EFFECT OF COMMON DISPARITY ON MONEY DEALING CONCLUSION IN LINK TO FISCAL EXCHANGE TOOLS – A STUDY WITH SPECIAL REFERENC TO TIRUNELVELI CITY - et al., Dr. S. Antony Raj (International Journal of Advanced Science and Technology, 2019)
In the modernistic ear, Money determines a prominent part in every one’s life. In other hand we have been facing both social and financial problems and to need to protect the future of mankind. For that people are indulging to invest their money in different capital movement. They are very much interested to invest their money in various purposes at the same time to expect perceived risk , return on investment ( gold ) invulnerability , credibility , merchantable , tariff benefit, formidable capital return, payback period etc. as well as believed that tangible outcome also .   Undoubtedly, Human has been having charismatic competent knowledge of experience, brand outfit, foresight knowledge, criticism, and deployment of capital, moral accountability; in participate the investment decision risk. More over woman has a potential power to involve all kind of filed.  They have participated in prevalent active part in decision making among the member of the family. For this glaring reason need to study to scrutinize gender disparity in holding financial uncertainty and identify the reason for gender disparity in their characteristics  between men and women in risk taking decision and to find out another reason that women totally differ from men thereby they have been taking more reactionary decision in the fiscal exchange than men.